The Role of Religious Education in Peace Building Process - Dr Rashid Ahmad (Hazara Islamicus, 2014)
No religion in the world teaches violence, insecurity of life and property as all religions have taught peace, security, forbearance, affection, patience, mercy, tolerance, justice, moderation, protection of humankind, co-existence and human dignity. Religion and extremism cannot go side by side while on the other hand religion, education and peace cannot be separated from one another. Religious education can counter extremist ideologies by creating awareness amongst people about their rights and duties. In this regard the role of religious institutions, madrassas, schools, colleges and universities is very important and a reformation of their syllabi is equally important. The role of churches, mosques, temples, pagodas, etc. is also of great importance. The role of the state is pivotal in curbing extremist ideologies through religious education by reformulating the educational objectives. This paper will focus on the issue to explore the effectiveness of religious education in countering violent ideologies